2017
DOI: 10.1136/vr.104281
|View full text |Cite
|
Sign up to set email alerts
|

Survival in 76 cats with epilepsy of unknown cause: a retrospective study

Abstract: Survival of cats with epilepsy of unknown cause (EUC) has not been reported. Seizure semiology and its relationship to treatment outcome and survival was studied in a population of 76 cats. A questionnaire for seizure semiology was developed based upon experimental data. Seizure semiology was characterized by owner interviews at least one year after discharge. Seizures were classified as: (1) primary generalized and (2) focal without and (3) with secondary generalization. Median age at seizure onset was four (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 39 publications
(92 reference statements)
0
23
0
Order By: Relevance
“…The age of seizure onset has been used as a diagnostic criterion for idiopathic epilepsy in dogs, with a ratio for age at onset established from 6 months to 6 years9. Interestingly, a younger age of onset has been reported in cats compared with dogs; in a study by Szelecsenyi, the range of seizure onset for cats with epilepsy of unknown cause was 3 months to 18 years 14. Therefore, early onset could also be considered to occur in the Iberian lynx with idiopathic epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…The age of seizure onset has been used as a diagnostic criterion for idiopathic epilepsy in dogs, with a ratio for age at onset established from 6 months to 6 years9. Interestingly, a younger age of onset has been reported in cats compared with dogs; in a study by Szelecsenyi, the range of seizure onset for cats with epilepsy of unknown cause was 3 months to 18 years 14. Therefore, early onset could also be considered to occur in the Iberian lynx with idiopathic epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Szelecsenyi and others 9 report that of the cats that died during the study period (24 of 76), the majority were epilepsy‐related deaths (66.6 per cent, n=16). This was defined by the authors as euthanasia motivated by circumstances directly associated with seizures.…”
Section: Feline Epilepsy and Euthanasiamentioning
confidence: 94%
“…In a recent small‐scale study, which included 18 cats with EUC, the one‐year survival rate was 73 per cent, which was significantly higher than the survival rate of cats with structural epilepsy or acute symptomatic seizures (35 per cent; 22 of 63 cats) 8 . A new study, summarised on p479 of this week's issue of Veterinary Record, 9 builds upon these findings in a larger population of 76 cats with EUC.…”
Section: Survival Analysis and Epilepsymentioning
confidence: 98%
See 1 more Smart Citation
“…In one study, up to 18% of cat owners elected not to start recommended antiepileptic drug (AED) treatment because of difficulty with PO administration. 7 Transdermal (TD) drug administration has been reported to be better tolerated and easier to administer than PO administration in cats. 8,9 In one study comparing PO and TD methimazole administration, 35% of cat owners reported missing at least one PO dose vs 8% during TD administration.…”
Section: Introductionmentioning
confidence: 99%